RELATIONSHIP BETWEEN LIFESTYLE AND DIET WITH BLOOD PRESSURE OF OUTPATIENT HYPERTENSION PATIENTS AT RSUD Dr. M.M DUNDA LIMBOTO - amelisa lawewan; titin dunggio; niluh arwati (Jurnal Ilmiah dr. Aloei Saboe, 2022)
This study aims to determine the relationship between lifestyle and diet with a blood pressure of outpatient hypertension patients at Dr. M.M Dunda Limboto hospital using a descriptive approach, univariate, and bivariate data analysis using a frequency distribution table and SPSS data analysis with Chi-Square test. Based on the results of the frequency distribution table shows that respondents with uncontrolled blood pressure are 44 respondents (64.7%) while those with controlled blood pressure are 24 respondents (35.3%). The results of this study indicate that there is a significant relationship between lifestyle and blood pressure of outpatient hypertension patients at Dr. M.M Dunda Limboto hospital with Chi-Square test results p = 0.035 (p <0.05) based on the results of the frequency distribution of respondents who experienced high blood pressure with an unfavorable lifestyle as many as 42 respondents (68.9%). As for diet, there is no significant relationship between diet and blood pressure of outpatient hypertension patients at Dr. MM Dunda Limboto hospital with Chi-Square test results p = 0.929 (p > 0.05) with the percentage of respondents who have a less frequent diet of 29 respondents (42.4%) while the pattern of eating less frequently is 39 respondents (57.4%).